Laparoscopic adrenalectomy: A single center experience - Kumar Suresh; Bera Moley; Vijay Mukesh; Dutt Arindam; Tiwari Punit; Kundu Anup (Journal of Minimal Access Surgery, 2010)
Aims : To evaluate the efficacy and safety of laparoscopic adrenalectomy in benign adrenal disorders. Methods and Material: Since July 2007, twenty patients have undergone laparoscopic adrenalectomy for various benign adrenal disorders at our institution. Every patient underwent contrast enhanced CT-abdomen. Serum corticosteroid levels were conducted in all, and urinary metanephrines, normetanephrines and VMA levels were performed in suspected pheochromocytoma. All the patients underwent laparoscopic adrenalectomy via the transperitoneal approach. Results : The patients were in the age range of 18-57 years, eleven males and nine females, seven right, eleven left, two bilateral. The mean operative time was 150 minutes (120-180), mean hospital stay four days (3-5), mean intraoperative blood loss 150 ml and mean post-operative analgesic need was for 36 (24-72) hours. One out of twenty-two laparoscopic operations had to be converted into open adrenalectomy due to intra-operative complications. Conclusions : Laparoscopic adrenalectomy is a safe, effective and useful procedure without any major post-operative complication and is the gold standard for all benign adrenal disorders.